Prevalence of hepatitis B virus among children of HBsAg-positive mothers in Hebron district, Palestine - Al-Amleh, Shefa (Translational Gastroenterology and Hepatology, 2020)
Background: Hepatitis B virus (HBV) is the major causative agent of chronic hepatitis causing liver cirrhosis and liver cancer. However, its transmission is likely to be minimized through vaccination. The study aims to determine the prevalence of hepatitis B among children born to hepatitis B surface antigen (HBsAg) positive women in Hebron district/Palestine. Methods: The overall number of women enrolled in this study was 125, all children of these mothers [386] were tested, out of which 42 were HBsAg-positive. The recruited participants were asked about their socio-demographic details including age, place of residence, occupation, level of education, as well as questions related to expected route of exposure to the virus and the type of vaccination they provided to their newborns. The results were explained based on the descriptive statistics that included frequencies and percentages. Results: The results showed that the prevalence of HBsAg among children born to HBsAg-positive mothers was 10.9% (42 positive children out of 386). Moreover, (33.6%) of the HBsAg-positive women had family history of hepatitis B infection. Transmission of hepatitis B among children of HBsAg-positive mothers was found in the low socio-economic class in the rural areas. Conclusions: The study concluded that the prevalence of HBsAg among children born to HBsAg-positive mothers was high among the families living in villages with low to moderate income.